Recent Advancements and Techniques Regarding the Roles of Pharmacists, Nutritionists, Nurses, Laboratory Technicians, and Other Healthcare Professionals in the Care of Cancer Patients: A Comprehensive Review - Dighriri, Ibrahim Mohammed; Alharthi, Adel Hulayyel; Alamri, Waleed Abdulrahman; Alzahrani, Turki Hassan; Alqarni, Sulaiman Abdullah; Alamri, Faisal Saleh; Alzahrani, Saeed Ahmed; Alharthi, Hamidi Saeed; AlMutarid, Qublan Dawood; Alyami, Ali hamad Dawood; Alyami, Hadi Saleh; AlMutarid, Mohammed Dawood; et al. (Journal of Ecohumanism, 2024)
Background: The paradigm of cancer care has evolved significantly, from a physician-centric model to a comprehensive multidisciplinary approach. Aim: This review analyzes the changing roles of healthcare personnel and technological advancements in modern cancer care. Results: Implementing advanced multidisciplinary care models resulted in notable enhancements in patient outcomes, namely, a 48% decrease in emergency department visits and a 43% decline in unplanned hospitalizations. Interventions by clinical pharmacists decreased medication errors by 42% and enhanced protocol adherence by 95%. Incorporating digital health technology boosted care coordination by 45% and improved infection control methods reduced healthcare-associated infections by 45%. Laboratory diagnostics have attained 99.8% accuracy in mutation detection with next-generation sequencing, transforming precision medicine methodologies in cancer. Conclusions: This study presents significant data demonstrating the beneficial effects of advanced healthcare professional roles and technological integration on cancer treatment. The results indicated superior patient outcomes, greater care coordination, and increased treatment efficacy using interdisciplinary strategies. Future research should standardize these improved methods across various healthcare environments and address implementation obstacles to provide fair access to enhancements in cancer care delivery.